A Study of Qur'anic Verses on the Concept of Musyarakah: Study of the Contextual Tafsir of Abdullah Saeed - Sopiyatun Sopiyatun; M Mujab (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
The paper wishes to present a study of verses of the Qur’an relating to cooperation in Abdullah Saeed’s view of profit sharing, an issue in the debate on Islamic banking in Indonesia. Researchers try to examine how Abdullah Saeed’s thoughts elaborate on profit sharing. Abdullah Saeed is an Australian scholar and scholar studying Islamic studies. He is an Omani Arabic and Islamic Studies Professor at the University of Melbourne. He is known for his progressive view on religious freedom in Islam.